Partnership Between Fintech Start-ups and Digital Payments for SMES in ASEAN - Ananda Priscilla Putri; Nenda Tegar Mainisa (Generate Digital Publishing, 2025)
Objective: This research aims to reveal the dynamics of collaboration between fintech start-ups and MSMEs in ASEAN, identifying the benefits and challenges faced in implementing fintech solutions in the MSME sector. Research Design & Methods: This research uses a qualitative method with a systematic literature review approach to analyze the collaboration between fintech start-ups and MSMEs in ASEAN. More than fifty articles, reports, and case studies from 2020 to 2024 were reviewed to explore the role of fintech in improving financial inclusion and MSME growth, particularly in six major ASEAN countries. Findings are categorized based on digital payment innovation, financial inclusion impact, and fintech's contribution to MSME development. Findings: The research found that collaboration between fintech start-ups and MSMEs in ASEAN improves financial inclusion, accelerates digitalization, and supports MSME business growth. Innovations such as digital payment systems and P2P financing facilitate MSMEs' access to financial services and working capital and strengthen competitiveness in six major ASEAN countries. Implications & Recommendations: This research shows the importance of collaboration between fintech start-ups and MSMEs to improve financial inclusion in ASEAN. It is recommended that governments and financial institutions support these partnerships through supportive policies, as well as improving financial literacy for MSMEs. Fintech start-ups are also expected to continue innovating to meet the local needs of MSMEs. Contribution & Value Added: This research provides new insights into the role of fintech in supporting MSME growth in ASEAN. Its contributions include a deeper understanding of fintech's impact on financial inclusion and opening up further research opportunities regarding its influence on competitiveness and job creation in the region.